1995
DOI: 10.1007/978-94-011-0333-6_28
|View full text |Cite
|
Sign up to set email alerts
|

On the Modeling of Grasps with a Multi-Fingered Hand

Abstract: This research investigates the stability of planar grasps with a multi-fingered robotic hand, using energy approach and geometric interpretation. A more general non-linear finger model was adopted, which reveals that the conditions for stability, obtained by traditional linearized model, are too relaxed. Geometrically, the critical conditions for the linearized planar model constitute a hyperplane in the space of grasping forces, whereas the non-linearized model constitutes a thirdorder surface contained withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Cutkosky and Kao (1989) were the first to provide a systematic method for determining the stability of a grasp when the compliance of the finger joints and links are included. Brodsky and Shoham (1995) investigated the stability of planar grasps. Howard and Kumar (1996) established a framework for analyzing the stability of grasps and showed that stability of a grasped object depends on the local curvature properties at the contacts as well as on the magnitude and arrangement of the applied forces.…”
Section: Introductionmentioning
confidence: 99%
“…Cutkosky and Kao (1989) were the first to provide a systematic method for determining the stability of a grasp when the compliance of the finger joints and links are included. Brodsky and Shoham (1995) investigated the stability of planar grasps. Howard and Kumar (1996) established a framework for analyzing the stability of grasps and showed that stability of a grasped object depends on the local curvature properties at the contacts as well as on the magnitude and arrangement of the applied forces.…”
Section: Introductionmentioning
confidence: 99%